Development and Evaluation of Targeted Antihypertensive Therapy Using Losartan-Encapsulated Nanoparticles - Dimri, Taniya; Jamal, Asif; K, Balachandar; Thakur, Pooja Dangi; N Shende, Savita; Govindarajan, Nidhya; C. Meshram, Pruthviraj; Pagore, Ramesh R. (Journal of Neonatal Surgery, 2025)
Hypertension is a widespread chronic condition and a major risk factor for cardiovascular diseases. Losartan, an angiotensin II receptor blocker, is commonly prescribed due to its efficacy and favorable safety profile. However, its therapeutic application is limited by poor oral bioavailability (approximately 33%), rapid hepatic metabolism, and frequent dosing requirements. This study aims to develop and evaluate a targeted nanoparticle-based drug delivery system for Losartan to enhance its pharmacokinetic and therapeutic profile. Losartan-loaded nanoparticles were formulated using the solvent evaporation method with polymers including PLGA, chitosan, and PEG derivatives. Formulation optimization was achieved through Box-Behnken Design, enabling the selection of the best-performing formulation based on particle size, zeta potential, drug loading (DL%), and encapsulation efficiency (EE%). The optimized PLGA-based formulation (F2) exhibited a mean particle size of 182.7 nm, zeta potential of –24.6 mV, DL% of 11.2, and EE% of 86.4. SEM analysis confirmed spherical shape with smooth surface morphology and no aggregation. In vitro drug release studies demonstrated a biphasic profile with an initial burst followed by sustained release over 48 hours. Kinetic modeling identified the Higuchi model (R² = 0.987) as the best fit, indicating diffusion-controlled release, while the Korsmeyer–Peppas model showed an anomalous transport mechanism (n = 0.61). Stability studies under ICH-recommended conditions confirmed long-term physical and chemical stability. These findings suggest that Losartan-loaded PLGA nanoparticles offer a promising approach for sustained, targeted antihypertensive therapy with improved bioavailability and reduced dosing frequency